Immunolocalization of estrogen and progesterone receptors in neuroendocrine tumors of lung, skin, gastrointestinal and female genital tracts - Bacchi, C.; Garcia, R. L.; Gown, A. M. (Lippincott-raven Publ, 1997)
Expression of estrogen (ER) and progesterone (PR) receptors has traditionally been associated with hormone-responsive organs, such as breast, ovary, and endometrium, and carcinomas arising therefrom. More recently, examples of ''unexpected'' ER or PR expression have been reported, particularly in tumors of endocrine tissues, such as thyroid and pancreatic islet cells. We tested the hypothesis that neuroendocrine tumors of various primary and metastatic sites might also express ER or PR or both by performing a retrospective immunohistochemical study in a series of 59 formalin- or mechacarn-fixed neuroendocrine carcinomas of various sites, including lung, skin, gastrointestinal and female genital tracts, and including carcinoid and atypical carcinoid tumors, small cell carcinomas, and Merkel cell carcinomas. We employed the anti-ER monoclonal antibody 1D5 and the anti-PR monoclonal antibody PgR1A6 using standard immunohistochemical techniques after microwave-based heat-induced epitope retrieval. Two of 28 carcinoid tumors demonstrated ER positivity; six of 30 cases were positive for progesterone receptor only. In addition, PR expression was found in one of two cases of atypical carcinoid, in five of 25 cases of small cell carcinoma, and in one of two cases of Merkel cell carcinoma. None of the atypical carcinoids, small cell carcinomas, or Merkel cell carcinomas were ER positive. In most cases, the fraction of tumor cell nuclei that were positive was <50%. These studies add the spectrum of neuroendocrine tumors that can express these hormone receptors. Similar to the pattern previously described in the subsets of meningiomas and islet cell tumors, PR but not ER is detectable in most cases. These results underscore the caution that should be exercised in determining tissue origin of metastatic carcinomas based only on detection of hormone receptors by immunohistochemistry.
Keywords: neuroendocrine tumor; carcinoid; small cell carcinoma; estrogen receptor; progesterone receptor; immunohistochemistry